Quantifying Surface Properties of Silica Particles by Combining Hansen Parameters and Reichardt's Dye Indicator Data - Stauch, Claudia; Süß, Sebastian; Luxenhofer, Robert; Binks, Bernard P.; Segets, Doris; Mandel, Karl (Particle & Particle Systems Characterization, 2018)
To obtain quantitative understanding of the effects of a chemisorbed organic modification on the surface of particles, the use of Reichardt's dye (RD) and Hansen solubility parameter (HSP) is discussed, whereby the S should be understood in terms of “similarity” rather than solubility as dispersibility is in focus. Silica nanoparticles modified to different extents with a medium chain silane including completely hydrophilic and hydrophobic particles are chosen. During spray-drying such particles form fully redispersible micro-raspberry superstructures. After qualitative estimations of the particles' polarity based on measuring both immersion time and ability of modified particles to stabilize oil–water emulsions, surface properties are quantified by HSP and RD. With increasing hydrophobicity, i.e., increasing amount of silane at the surface, all three contributions to HSP change. At the same time, RD analysis reveals that the normalized solvent polarity parameter decreases progressively. HSP and RD analysis are in good agreement, giving strong confidence on each method applied individually. This work demonstrates that after noticeable attempts for combined solubility parameters in case of molecules, carbon allotropes, and gelators, such studies can be extended toward functional (nano)particles and that a full picture of particle surface properties is possible via the combination of different, quantitative techniques.
CRIS-Team Scopus Importer:2020-04-02
Keywords: analytical centrifugation; colloidal stability; interface characterization; silica particles; surface coating